2022
DOI: 10.3390/ijerph19148725
|View full text |Cite
|
Sign up to set email alerts
|

Association of Academic Stress, Acne Symptoms and Other Physical Symptoms in Medical Students of King Khalid University

Abstract: Academic stress has varied effects on medical student life due to multiple factors, like study load, competition, frequent assessment, social pressure, etc. The authors of this paper conducted research to find the academic stress level and its sequel over acne and other physical symptoms on the medical students of King Khalid University (KKU), Saudi Arabia. A total of 168 participant responses were analyzed. Data collection was performed using a self-administered online questionnaire through the university web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The responses on the academic stress scale revealed that exams were the major cause of stress among students. In addition, overall academic stress was significantly positively associated with acne and physical symptoms [20].…”
Section: Introductionmentioning
confidence: 95%
“…The responses on the academic stress scale revealed that exams were the major cause of stress among students. In addition, overall academic stress was significantly positively associated with acne and physical symptoms [20].…”
Section: Introductionmentioning
confidence: 95%
“…Stress-related dietary habits and sleep deprivation increase systemic and skin-speci c in ammation, worsening acne severity. Neglecting skincare routines and improper use of skincare products can damage the skin barrier, making it more susceptible to acne-causing bacteria and environmental irritants [13,124,125].…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…In addition to the symptom causing enormous tragedies to the families, the unexpected death brought on by chronic fatigue has detrimental effects on social production [6]. Among the students, there are several factors that contribute to fatigue syndrome, including the amount of work they are engaged in, level of competition, frequent evaluations tests, and peer pressure [7]. Further, it is noted that the level of fatigue experienced by the students during an ongoing semester session and at the end of semester is based on the level of depression experienced during the semester session which also affects their functioning and health of affected students [8].…”
Section: Introductionmentioning
confidence: 99%